1992
DOI: 10.1007/bf02230875
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal dystonia due to a lesion of the cervical cord: Case report

Abstract: A 48 year old woman complained of mild weakness and paresthesias of the left limbs, followed 15 days later by episodes of paroxysmal dystonia of the left limbs occurring several times daily over 10 day period. Magnetic resonance imaging (MRI) of head and neck revealed a small area of altered signal in the T2-weighted sequences in the left posterolateral quadrant of the cord at the second cervical vertebra. An MRI scan 18 months later showed no lesion. This is the second case of paroxysmal dystonia with a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The authors found that the corticospinal tracts demonstrated dysfunction in all patients, while SSEPs remained normal [8] . The theory of corticospinal tract dysfunction or other long tract dysfunction, such a spinothalamic tract, is further supported by the case reports on cervical intramedullary tumors presenting with cervical dystonia [6,7] . Several studies have attempted and failed in differentiating idiopathic cervical dystonia from posttraumatic cervical dystonia [9,10] .…”
Section: Dear Editor mentioning
confidence: 51%
“…The authors found that the corticospinal tracts demonstrated dysfunction in all patients, while SSEPs remained normal [8] . The theory of corticospinal tract dysfunction or other long tract dysfunction, such a spinothalamic tract, is further supported by the case reports on cervical intramedullary tumors presenting with cervical dystonia [6,7] . Several studies have attempted and failed in differentiating idiopathic cervical dystonia from posttraumatic cervical dystonia [9,10] .…”
Section: Dear Editor mentioning
confidence: 51%
“…PKD associated with pure spinal cord lesions is rare 7,8 . Cosentino et al 7 reported a case of PKD associated with an intraspinal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The most common causes of secondary PxD, identified in a review of the literature, are MS, stroke or transient cerebral ischemia, trauma, metabolic abnormalities, central nervous system (CNS) infections, and anoxic brain injuries. Additional causes reported are thyrotoxicosis,12 Arnold‐Chiari malformation with syringomyelia,13 parasagittal menigioma,14 methylphenidate therapy,15 progressive supranuclear palsy,16 and spinal cord injury 17. Early recognition of potential causes is particularly important, as symptoms may be reversed if the underlying cause is identified and treated.…”
Section: Discussionmentioning
confidence: 99%